Numerical investigation on the blade load distribution in a pump as turbine - Bai, Xiaobang; Yang, Junhu; Wang, Xiaohui; Li, Jicheng (Frontiers in Energy Research, 2023)
Pump as turbine plays an important role in modern industrial process. One of the major goals of turbine design and optimization is to maximize its efficiency. Therefore, it is of great importance to connect force with work in the analysis process. In the present study, the three-dimensional flow field of the pump as a hydraulic turbine has been investigated in the steady-state mode. The load distribution along three captured streamlines (i.e. the shroud, hub and middle streamline) on both the pressure and the suction surface is observed, and the relationship between the load distribution and the working capability is systematically analyzed. The results show that the load distribution on the pressure surface of the hydraulic turbine blade gradually transitions from the reverse "S" shape to the "S" shape in the process of increasing, while the load distribution on the suction surface keeps increasing with a concave trend. The main work area of the fluid medium on the hydraulic turbine impeller is in the middle section of the blade. As the flow rate increases, the loads on the blade depict a linear decreasing trend from the inlet to the outlet. The net load acting on the blade is distributed in a concave parabola profile along the radial position of the blade. Focusing on the inlet and middle section of the blade profile in the design or optimization process of the hydraulic turbines will be more useful. This study provides a new analysis method for